2019
DOI: 10.31703/grr.2019(iv-iv).35
|View full text |Cite
|
Sign up to set email alerts
|

Linking Knowledge Management with Organizational Performance through Organizational Learning: Evidence from Higher Education Institutions in Pakistan

Abstract: The present study aimed to examine the mediating role of organizational learning in the relationship between knowledge management and organizational performance in HEIs, KP, Pakistan. Teachers working in the Universities were considered the sample (n=338) of the study. A structured questionnaire comprised items about research variables administered in order to collect data. Baron and Kennys (1986) four-step models applied through Preacher and Hayes (2013) Process macro as a data analysis technique. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…On the other hand perfect mediation was noted for HRM practices and Innovation & Creativity through KMC. These results are in line with the previous finding of K. Rehman et al (2019) stating that the knowledge resources of educational institutions can develop innovative courses, promote knowledge sharing, and help in gaining competitive advantage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand perfect mediation was noted for HRM practices and Innovation & Creativity through KMC. These results are in line with the previous finding of K. Rehman et al (2019) stating that the knowledge resources of educational institutions can develop innovative courses, promote knowledge sharing, and help in gaining competitive advantage.…”
Section: Discussionsupporting
confidence: 92%
“…Omotayo (2015) called knowledge equivalent to power and defined that "management of knowledge is the key to power" (p-2). The institutions of higher education in developing countries like Pakistan are important for national economy (K. Rehman, Khan, & Javed, 2019) and measures to maximize the performance are of vital importance in today's emerging economy of knowledge, for attaining and maintaining the competitive advantages (Pasha, 2012). The institutions of higher education create, maintain, and share knowledge and information, with the help of knowledge management capacity (KMC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to various frameworks, the impact of KM has been evaluated by several researchers. Rehman et al (2021) empirically observed how KM affects an organisation's learning and that knowledge acquisition and application were the most crucial factors in determining an organisation's performance. Singh et al (2021) examined the relationships between an organisation's innovation performance and KM techniques.…”
Section: Introductionmentioning
confidence: 99%
“…KMC, in its modern form, comprises the development of modern technological means, a proper environment for the utilisation of this technology, information acquisition and utilisation of the information (Bloom et al , 2016; Rashid et al , 2021). Organisational performance often aligns with the organisation’s KMC and knowledge-oriented leadership (Rehman et al , 2021). Acquiring KMC through knowledge and modern technologies associated with the process has become a prime focus for many organisations (Imran et al , 2022).…”
Section: Introductionmentioning
confidence: 99%